Language Planning and the Integration of the English Language in Algerian Primary Schools - Mouili, Fatiha; Kandouci, Amina (LANGUAGE ART, 2025)
The introduction of the English language in Algerian primary schools set the country on a crucial learning path. In this initiative, Algerian pupils will be prepared for a more globalized world as part of the Global Movement for Multilingualism. However, language planning and policy decisions, entailing a series of problems and the need to develop effective strategies, are significant factors impacting the success of this program. Thus, this study analyses the effective integration of English as a second language in Algerian primary schools, considering the country's multilingual and Arabic-speaking context. It aims to provide insights into the intricate relationship between language policies and classroom practices by reviewing challenges and strategies during this educational transition.